Distinctive Performance of Terahertz Photodetection Driven by Charge‐Density‐Wave Order in CVD‐Grown Tantalum Diselenide. (1st September 2019) - Wang, Lin; Wang, Jin; Liu, Changlong; Xu, Huang; Li, Ang; Wei, Dacheng; Liu, Yunqi; Chen, Gang; Chen, Xiaoshuang; Lu, Wei
Abstract: The quantum behavior of carriers in solid is the foundation of modern electronic and optoelectronic technology, but it is still facing huge challenges within inherited single‐particle quantum processes working at the millimeter wave/terahertz (THz) band. Here, a straightforward strategy for the direct detection of millimeter wave/THz photons in a sub‐wavelength metal‐TaSe2 ‐metal structure under strong interaction with a localized field of surface plasmon is proposed. By breaking the inversion symmetry under the perturbations of electric field and atomic reconstruction from van der Waals integration, the nonequilibrium electronic states under a radiant field can be manipulated in a collective fashion, leading to a large photocurrent responsivity over 40 A W −1 and noise equivalent power less than 1 pW Hz −1/2 even at room temperature. A more than 40‐fold enhancement in responsivity is achieved when transitioning from the normal phase to the CDW phase. The findings shed fresh light on the understanding of the delicate balance in the charge‐ordered phase, and facilitate the exploitation of a correlated electron system for optoelectronic applications in fields of security, remote sensing, and imaging. Abstract : Controlling the dynamic responses of different ordered phases has stimulated extensive research interests. Here, the implementation of a charge‐density‐wave (CDW) for terahertz detection is reported and its extremely high sensitivity driven by CDW distortion is demonstrated. The collective excitation combined with the strong interaction with long‐wavelength photons opens up novel feasibility toward realistic exploration of many‐body states for imaging and sensing applications.